Exploring the Structural Details of Cu(I) Binding to α-Synuclein by NMR Spectroscopy - Binolfi, Andrés (2010)
The aggregation of α-synuclein (AS) is selectively enhanced by copper in vitro, and the interaction is proposed to play a potential role in vivo. In this work, we report the structural, residue-specific characterization of Cu(I) binding to AS and demonstrate that the protein is able to bind Cu(I) with relatively high affinity in a coordination environment that involves the participation of Met1 and Met5 residues. This knowledge is a key to understanding the structural-aggregation basis of the copper-catalyzed oxidation of AS.